Assessment of Reactive powder concrete subjected to three different sodium sulfate Concentrations: Compressive Strength, Absorption, Porosity, Microstructure, and durability. (28th March 2022) - Bakhbergen, Umut; Shon, Chang-Seon; Zhang, Dichuan; Kryzhanovskiy, Kirill; Kim, Jong R.
Highlights: The compressive strength of RPC depends on Na2 SO4 solution concentration, w/b, and SF content. At low Na2 SO4 solution concentration, ettringite formation accumulated in the porous space leads to increasing the compressive strength of RPC. RPC has moderate to high resistance to external sulfate attack depending on Na2 SO4 solution concentration. As w/b decreases and SF content increases, the expansion of RPC is reduced. Abstract: Reactive Powder Concrete (RPC) is a relatively new type of concrete material characterized by very low water-to-binder ratios (w/b), the addition of supplementary cementitious materials like silica fume (SF), and the presence of very fine aggregates instead of conventional coarse aggregates. The durability of RPC with various w/b (0.18, 0.22, and 0.26) and SF content (15%, 20%, and 25%) against external sulfate attack (ESA) at various sodium sulfate (Na2 SO4 ) concentrations (0.35 M, 0.7 M and 1.4 M) was investigated in this study through examinations of compressive strength, expansion and mass change, microstructural characteristics, mineralogy, porosity, and sorptivity. The results indicated that: 1) owing to its improved microstructure, RPC could accommodate expansive products of ESA reactions, which can provide additional strength; 2) RPC showed very high resistance to Na2 SO4 attack under the ASTM C1012 criteria; 3) considerable sulfate ingress did not result in significant expansion and strength reduction for RPC mixtures at early stages of exposure, especially for the mixtures with high initial sorptivity and high interparticle connectivity; 4) considering the coupled effect of w/b and SF content on the number of RPC characteristics, mixture with w/b = 0.22 and 20% SF content showed the best performance upon exposure to ESA.